Functional and anatomical networks of executive control - Neubert, F (2009)
Actions are selected in the context of environmental demands and internal goals. Both change constantly and dynamically and several studies have addressed the issue of how information about these is represented, updated and integrated in the brain to form appropriate decisions and actions. The reprogramming of actions requires inhibition of movements or movement plans, resolution of response conflict and initiation of alternative actions. The right inferior frontal cortex (rIFC) and the presupplementary motor areas (pre-SMA) have been suggested to play a major role in response inhibition and action reprogramming. The degree to which inhibition of actions at a behavioural level can be related to physiological inhibition is unknown. Using single and paired-pulse transcranial magnetic stimulation (TMS), we investigated M1 excitability and M1 internal inhibitory mechanisms during action reprogramming (see Chapter 2.1.1). The temporal pattern of M1 excitability and M1 internal inhibitory mechanisms differed from those during normal action execution and could therefore play a causal role in action reprogramming. These findings are important as M1 is likely to be the site of convergence from different influences exerted by regions in the frontal lobes. In a second experiment we used paired-pulse TMS over rIFC and M1 to investigate functional rIFC-M1 interactions (see 2.1.2). We found that rIFC inhibited M1 excitability 175 ms after cue onset only in trials when actions needed to be reprogrammed and responses had to be inhibited, but not during normal action selection. In a third experiment we used a combined paired-pulse TMS – diffusion tensor imaging (DTI) approach to elucidate anatomical pathways of functional pre-SMA-M1 and rIFC-M1 connectivity (see 2.2). We found extended networks of executive control and action reprogramming. These results suggest that both, pre-SMA and rIFC influence motor output via premotor areas and fronto-basal ganglia loops. Different latency periods of rIFC-M1 and pre-SMA-M1 interactions were mediated by different white matter paths and networks. In a fourth experiment we tried to delineate the roles of rIFC and pre-SMA during action reprogramming using a combined paired-pulse TMS– repetitive TMS paradigm (see 2.3). The inhibitory influence exerted by rIFC over M1 during action reprogramming disappeared after mild and transient disruption of pre-SMA activity. Besides elucidating a network of brain areas associated with action reprogramming and movement inhibition these experiments have interesting methodological implications.